Problems of legal regulation on gender-based violence in Ukraine and foreign countries - T. S. Kyrychenko (Law and Safety)
The purpose of the article is to analyse gender-based violence and to study the legal mechanisms for overcoming it in Ukraine. On the basis of scientific findings and proposals, it has been suggested that a new perspective on this issue be taken. The basic concepts of gender-based violence, its forms, and European standards that are effective in preventing and combating violence have been studied. The expediency of forming a scientifically based system of prevention, regulation and overcoming of domestic violence has been emphasised. The legislation of different countries has been analysed, the peculiarities of gender-based violence and the factors that influence its occurrence in the family have been identified. The author’s own definition for the term “gender-based violence” has been presented.